2014
DOI: 10.1186/s12915-014-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared functions of plant and mammalian StAR-related lipid transfer (START) domains in modulating transcription factor activity

Abstract: BackgroundSteroidogenic acute regulatory protein (StAR)-related lipid transfer (START) domains were first identified from mammalian proteins that bind lipid/sterol ligands via a hydrophobic pocket. In plants, predicted START domains are predominantly found in homeodomain leucine zipper (HD-Zip) transcription factors that are master regulators of cell-type differentiation in development. Here we utilized studies of Arabidopsis in parallel with heterologous expression of START domains in yeast to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 42 publications
(68 reference statements)
5
54
0
Order By: Relevance
“…To further gain the mechanical insights of the post-transcriptional repression of ATML1, we performed domain deletion analyses. Among the four domains of ATML1, we focused on ZLZ and START domains because of their potential to interact with other regulatory molecules: the ZLZ domain is known as a dimerization motif and the START domain is predicted as a lipid/sterol-binding domain (Schrick et al, 2014). To assess the role of each domain in ATML1 localization, we generated transgenic lines that expressed 3xGFP-ATML1 fusion genes, with or without deletion of ZLZ or START, under the control of the ATML1 promoter ( proML1-3xGFP-ML1, proML1-3xGFP-ML1ΔZLZ and proML1-3xGFP-ML1ΔSTART).…”
Section: Zlz Domain Was Required For the Inhibition Of Atml1 Nuclear mentioning
confidence: 99%
See 1 more Smart Citation
“…To further gain the mechanical insights of the post-transcriptional repression of ATML1, we performed domain deletion analyses. Among the four domains of ATML1, we focused on ZLZ and START domains because of their potential to interact with other regulatory molecules: the ZLZ domain is known as a dimerization motif and the START domain is predicted as a lipid/sterol-binding domain (Schrick et al, 2014). To assess the role of each domain in ATML1 localization, we generated transgenic lines that expressed 3xGFP-ATML1 fusion genes, with or without deletion of ZLZ or START, under the control of the ATML1 promoter ( proML1-3xGFP-ML1, proML1-3xGFP-ML1ΔZLZ and proML1-3xGFP-ML1ΔSTART).…”
Section: Zlz Domain Was Required For the Inhibition Of Atml1 Nuclear mentioning
confidence: 99%
“…ZLZ and START domains were shown to interact with other molecules or act as target sites for post-translational modification (Tron et al, 2002;Schrick et al, 2014). It has been reported that the START domain of ATML1 stimulated transcription factor activity in yeast in response to increased sterol biosynthesis (Schrick et al, 2014). Therefore, HD-ZIP class IV START domains may be involved in post-translational activation of transcription factors.…”
Section: Deletion Of Zlz Caused Accumulation Of Atml1 In the Inner Cementioning
confidence: 99%
“…Steroidogenic acute regulatory protein (STAR) related to lipid transfer plays a key role in the acute regulation of steroid hormone synthesis by enhancing the conversion of cholesterol into pregnenolone [25]. There is evidence that cholesterol plays a direct role in inflammation which promotes muscle building and strength [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PITPα present in the same experiment extracted phosphatidylcholine (PC) and phosphatidylinositol (PI) but not cholesterol (data not shown). Therefore, the lack of recovery of the major phospholipids, including PC, PI, phosphatidylserine (PS) and phosphatidylethanolamine (PE), by Lam4S2 indicates that if it does bind phospholipids non-specifically (Schrick et al, 2014), such binding can only be weak (Kd >100 μM).…”
Section: Start-like Domains In Ysp2p and Lam4p All Solubilize Sterolmentioning
confidence: 99%